CHANGES IN PHYSICAL AND CHEMICAL PROPERTIES OF ORAL FLUID IN PATIENTS WITH PERIODONTAL DISEASES IN THE SETTINGS OF CHRONIC HEPATITIS C DURING ANTIVIRAL THERAPY - H.A. Sichkoriz; L.Yu. Minko (Український стоматологічний альманах, 2018)
The results represent the study of changes in physical and chemical properties of oral fluid in 31 people with chronic hepatitis C (CHC) who received antiviral treatment (AVT). It was found that the changes in physical and chemical properties of oral fluid were more pronounced in patients with periodontal diseases (PD) in the settings of chronic hepatitis C during antiviral therapy compared with patients without the history of CHC. The increase in violations of these parameters is observed on the 1st-3rd months of AVT and characterized by decreased rate of stimulated secretion and increased viscosity of the mixed saliva, shift of acid-base balance toward acidosis and reduced buffer capacity. The negative dynamics of physical and chemical properties of oral fluid during AVT requires correction to prevent the development of PD and reduce the number of complications.